2019
DOI: 10.1017/s0007114519001600
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a) concentration is associated with plasma arachidonic acid in subjects with familial hypercholesterolaemia

Abstract: Elevated lipoprotein(a) (Lp(a)) is associated with CVD and is mainly genetically determined. Studies suggest a role of dietary fatty acids (FA) in the regulation of Lp(a); however, no studies have investigated the association between plasma Lp(a) concentration and n-6 FA. We aimed to investigate whether plasma Lp(a) concentration was associated with dietary n-6 FA intake and plasma levels of arachidonic acid (AA) in subjects with familial hypercholesterolaemia (FH). We included FH subjects with (n 68) and with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…A meta-analysis study demonstrated a reduction in the risk of cardiovascular events by increasing PUFAs intake [ 2 ]. It is noteworthy that arachidonic acid (AA), one of the most abundant PUFAs in the human body, is a long-chain polyunsaturated omega-6 fatty acid containing 20 carbon atoms and 4 double bonds (20:4, n-6), and its role in cardiovascular function has been revealed in recent studies [ 3 , 4 , 5 , 6 ]. AA has several physiological functions: as a constituent in the phospholipid bilayer of cell membranes, as a precursor for a crucial group of biologically active compounds known as eicosanoids (C 20 unsaturated lipids), as a regulator of gene expression, as inflammatory intermediator, and as vasodilator/vasoconstrictor [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis study demonstrated a reduction in the risk of cardiovascular events by increasing PUFAs intake [ 2 ]. It is noteworthy that arachidonic acid (AA), one of the most abundant PUFAs in the human body, is a long-chain polyunsaturated omega-6 fatty acid containing 20 carbon atoms and 4 double bonds (20:4, n-6), and its role in cardiovascular function has been revealed in recent studies [ 3 , 4 , 5 , 6 ]. AA has several physiological functions: as a constituent in the phospholipid bilayer of cell membranes, as a precursor for a crucial group of biologically active compounds known as eicosanoids (C 20 unsaturated lipids), as a regulator of gene expression, as inflammatory intermediator, and as vasodilator/vasoconstrictor [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, mediation analysis failed to show an important role for any of the saturated FAs, in mediating the effect of surgery versus lifestyle intervention on Lp(a) levels in trial 1, an important result the current study adds to the existent knowledge. It has previously been shown that plasma levels of AA were positively associated with Lp(a) levels in patients suffering from familial hypercholesterolemia [9]. AA is an antagonist of the farnesoid X receptor (FXR) [37], and FXR activation has been found to decrease Lp(a) levels [38].…”
Section: Comparisons With Other Studies-what Does the Current Work Ad...mentioning
confidence: 99%
“…Lp(a) levels may also be regulated, to some extent, by changes in plasma fatty acids (FAs). A positive, novel association between plasma levels of the n-6 FA arachidonic acid (AA) and Lp(a) in patients with familial hypercholesterolemia has recently been shown [9]. Other studies have shown that an increased intake of total-and saturated fat is accompanied by a decrease in Lp(a) levels [10][11][12][13], and that supplementation of conjugated LA lead to increased Lp(a) levels [14].…”
Section: Introductionmentioning
confidence: 99%
“… 6 However, dietary intake, including fats, have only a small direct impact on Lp(a) levels (typically a few mg/dL change at most). 7 10 Despite there being only a small impact of diet on Lp(a) levels, dietary approaches may help to mitigate the risk associated with Lp(a). In two large cohort studies it was found that those following healthier lifestyle patterns had much lower risk for ASCVD despite higher Lp(a) levels.…”
Section: Introductionmentioning
confidence: 99%